1981
DOI: 10.1177/002246698101500307
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies of Effects of Artificial Food Colors On Hyperactivity

Abstract: The double-blind, double-crossover study tested Feingold's hypothesis that synthetic food colors cause hyperactivity in some children. Each of 6 hyperactive boys constituted a singlesubject experiment. All subjects were on the Feingold diet eliminating artificial colors and flavors. All mothers claimed the diet had been effective. Subjects were challenged twice, for 3-day periods, with synthetic colors introduced in cookies eaten on challenge days. Identically appearing and tasting cookies containing no synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Fourteen studies, 15,19,20,24,34,42,45,47,49,51,52 including three studies reported by Conners, 19 attempted to gauge the percentage of children reacting to food colors. All were based on children who had been preselected to be diet responsive by either an open-label trial or parent report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies, 15,19,20,24,34,42,45,47,49,51,52 including three studies reported by Conners, 19 attempted to gauge the percentage of children reacting to food colors. All were based on children who had been preselected to be diet responsive by either an open-label trial or parent report.…”
Section: Resultsmentioning
confidence: 99%
“…Across all 14 reports (n = 241, with 51 “responders”), the event rate was 18% (95% CI = 0.09–0.32; p < .0001). Among the eight studies with what we coded as using well-defined criteria for responders, 15,17,19,20,24,46,47,49 in (n = 176), including two studies in Goyette et al, 17 the event rate was 24% (95% CI = 0.13–0.40; p = .002). Variation among the studies was high (Q = 17.9; p < .01).…”
Section: Resultsmentioning
confidence: 99%
“…With the majority of studies conducted before 1990, diagnostic criteria used for sample selection were largely outdated, which raises concerns about the generalizability of results to an ADHD population. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][57][58][59]61,62 The outcome assessment methodology used in the majority of studies lacks consistency with current standards for ADHD assessment, which require measuring change in both symptoms of the disorder and functional impairments associated with the disorder and ensuring that measurements are made in multiple settings with multiple informants and different methodologies. 63 These discrepancies raise questions concerning the reliability of the conclusions drawn in these studies.…”
Section: Overview Of Existing Research On Food Additives and Adhdmentioning
confidence: 99%
“…The Feingold K-P diet requires an abrupt change in lifestyle since increased vigilance is necessary in grocery shopping and food preparation, families generally cannot eat at restaurants, and the child cannot eat school lunches (Brenner 1977, Cook & Woodhill 1976, Sheridan & Meister 1982, Spring, Vermeersch, Blunden & Sterling 1981. Lew (1977) conducted a four week trial of the Feingold K-P diet on her family and concluded that "the Feingold Diet is indeed a very different and very difficult diet to maintain in practice.…”
Section: Resultsmentioning
confidence: 99%